Evaluasi Otoritas Bawaslu Dalam Penegakan Hukum Pemilu Terkait Politik Transaksional pada Pemilu Legislatif Dalam Perspektif Teori Gap Implementasi - Linggar Vandito, Revo; Febrian, Adly; Anak Anugrah, Ave; Nutthoriq, Fathir; Lisa Paramita, Monika; Rahmawati, Restu (STISIPOL Raja Haji, 2024)
In the context of the quality of elections, transactional politics and money politics have always been a bug in the quality of elections in Indonesia. In the context of election law enforcement, including related to transactional politics, Bawaslu is an institution established to enforce election law, including money politics. Unfortunately, various data show that money politics is still the dominant political strategy in elections. This research seeks to prove that there is an implementation gap between Bawaslu's authority in enforcing electoral law and the existing reality and find out what factors cause the implementation gap. In addition, this research seeks to provide recommendations regarding the existing implementation gap. This research uses descriptive qualitative research with data collection methods of literature study and document study which are correlated with the existing theoretical basis. The result of this research is that there are several things that cause the implementation gap such as the difficulty of defining money politics which is a systemic problem in policy capacity theory. The recommendations presented in this study are First, the need to strengthen the role of Bawaslu as an election supervisory institution by providing more comprehensive authority in the investigation and examination process. Second, there is a need for a firmer and clearer legal change related to money politics, as well as an increase in sanctions for violators.